Display : International Exhibition of painting. - Andersen, Mikael; Bang Larsen, Lars; Kern, Kristine; Misfeldt, Mai; Rasmussen, Malene la Cour (Kobenhavn : Charlottenborg Exhibition Hall, 1997)
Ackermann, Rita ; Beecroft, Vanessa ; Bonde, Peter ; Bonin, Cosima von ; Carstensen, Claus ; Christiansen, Jesper ; Cranston, Meg ; Diamond, Jessica ; Edefalk, Cecilia ; Forslund, Leonard ; Förg, Gunther ; Heilmann, Mary ; Hume, Gary ; Kelley, Mike ; Kilimnik, Karen ; Kippenberger, Martin ; Krystufek, Elke ; Magnússon, Tumi ; McCarthy, Paul ; Miller, John ; Oehlen, Albert ; Rasmussen, Christian S. ; Shaw, Jim ; Strode, Thaddeus
biog., tent. p. 66-75
Engels
Display : International exhibition of painting, Charlottenborg Exhibition Hall, Kobenhavn, September 13 - Ocotber 19, 1997
boek